Does Therapists' Disengaged Feelings Influence the Effect of Transference Work? A Study on Countertransference. (25th April 2016) - Dahl, Hanne‐Sofie Johnsen; Høglend, Per; Ulberg, Randi; Amlo, Svein; Gabbard, Glen O; Perry, John Christopher; Christoph, Paul Crits
Abstract : Exploration of the patient–therapist relationship (transference work) is considered a core active ingredient in dynamic psychotherapy. However, there are contradictory findings as for whom and under what circumstances these interventions are beneficial. This study investigates long‐term effects of transference work in the context of patients' quality of object relations (QOR) and therapists' self‐reported disengaged feelings. Therapists' disengaged feelings may negatively influence the therapeutic process, especially while working explicitly with the transference since discussing feelings that are present in the session is an essential aspect of transference work. One hundred outpatients seeking psychotherapy for depression, anxiety and personality disorders were randomly assigned to one year of dynamic psychotherapy with transference work or to the same type and duration of treatment, but without transference work. Patients' QOR‐lifelong pattern was evaluated before treatment and therapists' feelings were assessed using the Feeling Word Checklist‐58 after each session. Outcome was measured with self‐reports and interviews at pre‐treatment, mid‐treatment, post‐treatment, one year and three years after treatment termination. A significant interaction of treatment group (transference work versus no transference work) by QOR by disengaged therapist feelings was present, indicating that disengaged feelings, even small amounts, were associated with negative long‐term effects of transference work, depending on QOR Scale scores. The strengths of the negative association increased significantly with lower levels of QOR. The negative association between even a small increase in disengaged therapist feelings and long‐term effects of transference interpretation was substantial for patients with poor QOR, but small among patients with good QOR. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioner Message: Therapists' emotional reactions to their patients (countertransference) seem to have a significant impact on both the treatment process and outcome of psychotherapy. Therapists' heightened level of disengaged feelings over a treatment period shows an adverse impact on the effect of transference work for all patients, and especially so for patients with a history of poor, non‐mutual and complicated relationships. For patients with a history of reciprocal, sound relationships the negative influence of therapists' disengaged countertransference is minimal. Higher therapist disengagement is strongly related to inferior therapists' skill for patients with a history of poor relationships and/or more personality disorder pathology. Training and supervision should provide direct feedback and focus on therapists' internal thought processes and emotional reactions. Therapists need to recognize and understand their feelings and attitudes in order to use the countertransference as a tool to understand the interpersonal process in therapy.